IDENTIFIKASI KEPATUHAN PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RSU B: IDENTIFICATION OF COMPLIANCE WITH NURSING CARE DOCUMENTATION IN THE INPATIENT ROOM RSU B - Faidah, Nurul; Resiyanthi, Ni Komang Ayu (Stikes Wira Medika Bali, 2019)
Compliance with nursing documentation is a legal aspect of nursing. Nursing Care Documentation consists of assessment, nursing diagnoses, interventions and evaluations. Documentation plays an important role in all kinds of demands and is a form of effort to foster and maintain nurse and nursing accountability. The purpose of this study was to determine the compliance of nursing care documentation in the inpatient ward of RSU B. The method used was cross-sectional number of samples in this study as many as 33 people. In this research descriptive data analysis. With the results of the study of female gender 60.6%, age 69.7%> 35 years, education 63.6% Nursing, 60.6% work period of more than 3 years and the results of compliance documenting nursing care 63.6% obedient. Researchers suggest that health services increase nurses' knowledge by providing workshops or training in documenting nursing care to improve nurse compliance in nursing care documentation